Islamic Education and the Ethics of Peacebuilding in a Pluralistic World - Alvi, Mohd Rabe (Afeksi: Jurnal Penelitian dan Evaluasi Pendidikan, 2025)
This study explores the pivotal role of Islamic education in fostering peace and tolerance within contemporary societies, particularly through the lens of Islamic curriculum frameworks designed to counter extremism and promote harmonious coexistence. By critically analyzing educational content, pedagogical approaches, and institutional objectives, the research highlights how Islamic teachings rooted in the Qur’an and Sunnah emphasize values such as compassion, justice, and mutual respect. The study examines various peace-oriented educational programs and curricula implemented in different Islamic contexts, assessing their effectiveness in deconstructing radical ideologies and nurturing a culture of non-violence. Through qualitative analysis and case studies, the paper demonstrates that a well-structured Islamic curriculum, grounded in authentic religious principles and integrated with modern educational methodologies, significantly contributes to the prevention of radicalization and the promotion of societal peace. The findings underscore the need for a transformative educational approach that empowers learners with critical thinking, interfaith understanding, and ethical responsibility, ultimately supporting global efforts in counter-terrorism and peacebuilding.